Perjuangan Perjuangan Perempuan pada Film Send Me to the Cloud - Hervita Thalia; Intan Erwani (Signifiѐ, 2023)
ABSTRACT: In this era women continue to voice the movement of feminism for the rights to be equal to men. The struggle of women is described through literary such as the film. The purpose of this study is to find out the struggle of women in the film Send Me to the Cloud. The research method uses descriptive qualitative from Sugiyono and Mile & Huberman data analysis techniques, and uses the theory of Feminism Beauvoir (1956). The results of this study in the form of a struggle for 1) Diagnosis of ovarian cancer, 2) Patriarchy parents, 3) need a partner